DEATH SENTENCE FOR DRUG TRAFFICKERS ACCORDING TO HADITH NARRATED BY AHMAD - Masykur, Basmah Ahmad (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Abstract Drug abuse and trafficking represent significant global challenges, particularly in Indonesia. This study examines the Islamic perspective on the death penalty for drug traffickers, referencing the Hadith narrated by Ahmad. The research highlights Islam's emphasis on community health and safety, categorizing drug use as a major sin warranting severe sanctions. Employing a comparative normative legal approach, the analysis incorporates Islamic jurisprudence, national laws, and scholarly opinions. While some Islamic scholars endorse the death penalty as a means of justice and societal protection, others urge caution, advocating for measured applications rooted in fairness and due legal processes. Findings suggest that Islam recognizes the grave societal harm caused by drug trafficking, supporting stringent measures like the death penalty under a transparent legal framework. The study underscores the necessity of balancing justice, human rights, and religious principles in addressing this critical issue.